Tadeusz Wallas, Beata Przybylska-Maszner, Maciej Walkowski (ed.), EU external actions in the contested global order, Wydawnictwo Wydziału Nauk Politycznych i Dziennikarstwa, Poznań 2022, ss. 233. - Adamiszyn, Aleksandra (Rocznik Integracji Europejskiej, 2022)
Recenzja